Pertumbuhan dan Hasil Karabenguk (Mucuna pruriens) sebagai Tanaman Penutup Tanah pada Dua Musim Berbeda - Supriyono Supriyono; Tohari Tohari; Abdul Syukur; Didik Indradewa (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This research does to known: 1) the effect of season, 2) the effect of cover crop kind and organic fertilizer, and 3) the interaction of two factors on growth and yield of velvet bean as cover crops. This research was conducted in Tancep, Ngawen, Gunungkidul at 170 m usl, litosol, 5-17 cm level of soil tillage, 9-10o elevation level, was started at December 2002 and finished at August 2003.